2012
DOI: 10.1007/s10909-012-0543-5
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Anisotropy and Impurity Scattering in Ge at mK Temperatures: Modeling and Comparison to Experiment

Abstract: Improving upon the present background rejection capabilities of the cryogenic germanium detectors for direct dark matter search involves an in-depth comprehension of the charge collection process in these devices. Experimental data point to the combined effects of lattice and impurity scattering on the anisotropy of electron transport in Ge at mK temperatures. A Monte Carlo simulation code has been implemented to incorporate these features in a consistent model for charge collection. In a novel approach to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Detailed Monte Carlo studies in CDMS [36,37,56,57,[64][65][66] and EDELWEISS [67,68] detectors can be found in the literature. These studies include discussion of quantities which are relevant in the tuning and their effects on phonon pulse shape, charge transport, TES phase-separation and TES noise.…”
Section: E Numerical Constants For Tes Simulationmentioning
confidence: 99%
“…Detailed Monte Carlo studies in CDMS [36,37,56,57,[64][65][66] and EDELWEISS [67,68] detectors can be found in the literature. These studies include discussion of quantities which are relevant in the tuning and their effects on phonon pulse shape, charge transport, TES phase-separation and TES noise.…”
Section: E Numerical Constants For Tes Simulationmentioning
confidence: 99%
“…There results a complex, bias dependent pattern of charge collection between the different measurement channels. 2,3 Application of a magnetic field leads to further changes in the collection patterns, as figure 3 (a) shows for the field in the direction normal to the detector axis. On the other hand, minute effects only are observed in the c and d channels when the field is turned parallel to the detector axis ( fig.…”
Section: Resultsmentioning
confidence: 98%
“…Experiments reported elsewhere in these proceedings demonstrate large differences between electron and hole collection in Ge detectors at mK temperatures, with regard to carrier straggling especially. [2][3][4][5] These differences are also reflected in the magnetic field effects ( figs. 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed analysis of the charge collection patterns in these devices is presented in a companion paper in these proceedings, 10 based on Monte Carlo simulations of carrier transport taking into account the combined effects on electron motion of intervalley and impurity scattering processes.…”
Section: Discussionmentioning
confidence: 99%